Barthes, fotografia, haikai: a isenção do sentido - Bueno, Iury Carlos (2017)
The present research is dedicated to a reflection on the possible relations between photography and haikai in the work of Roland Barthes, including those works of the author that can illustrate them: The Empire of Signs (1970), The Neutral (1977-1978), The Preparation of Romance (1978-1979) and Camera Lucida (1980). More specifically, we will focus on the concept of "punctum" in the light of the insistent notes on the instantaneousness of haiku that are disseminated in the barthesian text, proposing a nexus between literature and image. We hypothesize that "punctum" is the last manifestation of "zero degree" or "neutral", understood as a problematic stronghold of meaning that escapes the paradigm of meaning. The main corpus of the research comprises the barthesian texts in which we astonish said intersection and meetings. The theoretical references involve a state of the art of barthesian studies (Calvet, Marty, Batchen and among us Motta, Perrone-Moisés), the most relevant works on photography (Dubois, Soulages, Rouillé, Frade, Sontag) and studies on haiku (Blyth, Paz, Herrigel, Keene, and among us Franchetti, Leminski, Verçosa, Campos)